A Comparative Analysis of the Influence of Temperature and Wind Speed on the Efficiency of 100 WP Solar Panels of Monocrystalline and Polycrystalline Types at Sriwijaya State Polytechnic - Nurhaida; Susanti, Indah; Puspitasari, Dela Urbach (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
Solar panels in PLTS convert photon energy into electrical energy, where sunlight, which produces light intensity, plays a very important role. In this case, environmental conditions that continue to change can affect the output power of the solar panels. Apart from light intensity, solar panel environmental conditions such as temperature and wind speed greatly affect the efficiency of solar panels. This research looks at the extent of the influence of temperature and wind on the efficiency of solar panels. From the test results and calculations, it was found that the sample temperature of the monocrystalline panel measured on Friday, June 16, 2023, was 31.5°C, and the temperature of the polycrystalline panel was 31°C. From various aspects of the calculations carried out, we can see that the efficiency of monocrystalline panels is 18.07%, while the efficiency of polycrystalline panels is 16.04%. From the calculation results, we can conclude that the efficiency of monocrystalline modules increases significantly.